2017
DOI: 10.2514/1.j054943
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Comparison of Aerofoil Shape Parameterization Methods

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Department of Aerospace Engineering, University of BristolA comprehensive review of aerofoil shape parameterisation methods that can be used for aerodynamic shape optimisation is presented. Seven parameterisation methods are considered for a range of design variables: CSTs; B-Splines; Hicks-Henne bump functions; a Radial Basis function (RBF) domain element appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 47 publications
(61 reference statements)
0
73
0
Order By: Relevance
“…Other work by the authors 42 has shown that for aerofoil approximations the errors in drag coefficient prediction for transonic Euler flow relative to a target aerofoil are roughly equivalent to the maximum geometric error. These results therefore suggest that if the eight subdivision level is used for an inviscid drag reduction case, the design space should include aerofoils within the order of a thousandth of a drag count of any optimum.…”
Section: A Geometry Matchingmentioning
confidence: 99%
“…Other work by the authors 42 has shown that for aerofoil approximations the errors in drag coefficient prediction for transonic Euler flow relative to a target aerofoil are roughly equivalent to the maximum geometric error. These results therefore suggest that if the eight subdivision level is used for an inviscid drag reduction case, the design space should include aerofoils within the order of a thousandth of a drag count of any optimum.…”
Section: A Geometry Matchingmentioning
confidence: 99%
“…The method is based on perturbations, so is independent of the initial geometry and can fit into any of the three categories outlined above; the deformative formulation is used in this work, to allow a unified application of the design variables to control both the surface and volume mesh within the ASO framework. Previous work has considered the method's ability to represent a wide-range of aerofoil shapes (Poole et al 2015;Masters et al 2017b), and their effectiveness in aerofoil optimisation (Poole et al 2017;Masters et al 2017a), wherein the efficiency of this modal approach was clearly demonstrated. Hence, the aim of the work presented here is to develop an effective method to apply these novel mathematically-extracted design variables, which have been extracted as two-dimensional quantities, in three dimensions, and determine their effectiveness when applied to aerodynamic optimization, in particular drag minimisation of wings in transonic flow.…”
Section: Shape Parameterizationmentioning
confidence: 99%
“…Methods are classified as either constructive, deformative or unified. In-depth reviews have been presented by Samareh (2001b), Castonguay and Nadarajah (2007), Mousavi et al (2007) and Masters et al (2017b).…”
Section: Shape Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial amount of research has been published for a number of decades in the field of ASO; reviewlike works have been presented in parameterization [10], and optimizer performance [11,12]. One primary issue on the development of the research field has been a lack of consistent benchmarking of individual ASO frameworks on unified test cases.…”
Section: Introductionmentioning
confidence: 99%